EFEKTIVITAS PENGAJIAN MALAM JUM’AT DALAM MEMBANGUN KARAKTER ISLAMI REMAJA PEREMPUAN DI DESA AEK GALOGA MANDAILING NATAL - Mela Sari; Syamsiah Depalina (CV. Denasya Smart Publisher, 2025)
Non-formal education plays a significant role in supporting the development of Islamic character, particularly among adolescents. The Friday night study (pengajian) sessions, as a form of community-based religious education, serve as a potential medium for spiritual and moral guidance in rural areas. This study aims to analyze the effectiveness of Friday night study sessions in shaping the Islamic character of female adolescents in Aek Galoga Village, Mandailing Natal Regency. This research employs a qualitative method with a phenomenological approach, focusing on the lived experiences of the participants. Data were collected through observation, in-depth interviews, and documentation. The findings indicate that the regular study sessions contribute to instilling Islamic values such as discipline, social awareness, politeness, and a stronger understanding of religious teachings among the youth. Moreover, these activities foster social cohesion and help create a religious environment that supports moral development. Thus, the Friday night study sessions are proven to be an effective medium for building the Islamic character of female adolescents in the village setting.